Pelaksanaan Pemeriksaan Kehamilan Di Puskesmas Garongkong Desa Sumpang Binagae Kabupaten Barru - Rosida, Rosida; Fitri, Lidia; Latif, Sarifudin Andi; Leli, Leli; Saad, Rahmiyani; Jariyah, Ainun (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Danger signs of pregnancy must be recognized and detected early so that they can be treated properly because every danger sign of pregnancy can result in pregnancy complications. Based on research, every pregnancy can have potential and carry risks for the mother. The aim of this PkM is pregnancy checks and outreach about understanding the danger signs in pregnancy, increasing public awareness about the importance of knowing the danger signs that will occur in pregnancy and providing information on the benefits of knowing the danger signs in pregnancy. Method This activity is divided into two stages through communication media regarding material on danger signs in pregnancy and using Lefleat for danger signs in pregnancy. The targets for this PkM activity are mothers in the Garongkong Community Health Center working area, Barru Regency. Results: In this service activity, the pre-test results showed that 4 people (40%) had good knowledge and 6 people (60%) had sufficient knowledge regarding the danger signs of pregnancy. It is hoped that outreach and counseling activities for pregnant women will motivate and change behavior in pregnant women. Husbands and families are expected to play an active role and recognize and take pregnant women to health workers as soon as possible, cadres are expected to play an active role in finding pregnant women who are at high risk and it is hoped that local community leaders will participate in activities to provide immediate assistance if an emergency occurs, especially for pregnant women.